Components, criteria and levels of formation of the readiness of future geography teachers for professional activity - Shorobura, Inna; Adobovska, Mariia (Journal of Education, Health and Sport, 2017)
The article defines and theoretically substantiates the components, criteria and levels of formation of the readiness of future geography teachers for professional activities using interactive technologies. It is noted that the preparedness of future teachers for professional activities should be considered as a system that integrates the motivational-targeted, cognitive-meaningful, operational-activity and evaluative-reflective components. Criteria and indicators were also developed to assess the level of readiness of a future geography teacher for professional activities. An introduction to the practice of teaching interactive technologies is proposed, which contribute to greater independence of students’ academic work, flexibility and multi-level.